Tetra‐benzothiadiazole‐based [12]Cycloparaphenylene with Bright Emission and Its Supramolecular Assembly. Issue 47 (7th September 2020) - Qiu, Zhen‐Lin; Tang, Chun; Wang, Xin‐Rong; Ju, Yang‐Yang; Chu, Ke‐Shan; Deng, Ze‐Ying; Hou, Hao; Liu, Yu‐Min; Tan, Yuan‐Zhi
Abstract: The radial conjugated π‐system of cycloparaphenylenes (CPPs) makes them intriguing fluorophores and unique supramolecular hosts. However, the bright photoluminescence (PL) of CPPs was limited to the blue light and the supramolecular assembly behavior of large CPPs was rarely investigated. Here we present the synthesis of tetra‐benzothiadiazole‐based [12]cycloparaphenylene (TB[12]CPP), which exhibits a lime to orange PL with an excellent quantum yield up to 82 % in solution. The PL quantum yield of TB[12]CPP can be further improved to 98 % in polymer matrix. Benefiting from its enlarged size, TB[12]CPP can accommodate a fullerene derivative or concave–convex complexes of fullerene and buckybowl through the combined π–π and C−H⋅⋅⋅π interactions. The latter demonstrates the first case of a ternary supramolecule of CPPs. Abstract : A benzothiadiazole‐based [12]cycloparaphenylene (TB[12]CPP) is obtained and characterized. TB[12]CPP exhibits a lime to orange emission with a quantum yield up to 98 %, ranking it as one of the brightest CPPs. As a supramolecular host, TB[12]CPP is bright as well, showing adaptable ring structure. A ternary assembly between TB[12]CPP, fullerene, and buckybowl is realized.